Financing economic development: A structural approach to monetary policy - FitzGerald, E; Vos, R (Gower, 1989)
Eight papers, intended to serve macroeconomic policy-making in third world countries, explore the construction of a complete theory of finance. Papers examine the foundations of development finance; monetary policy and financial development; the analytics of stabilization policy in the small semi-industrialized economy; international finance, global adjustment, and North-South relations; stability and stabilization in Thailand; windfall gains, unbalanced growth, and stabilization in Ecuador; money and the agrarian question in Mozambique; and accumulation, defense, and income distribution in Nicaragua, 1979-86. Contributors are Karel Jansen, Marc Wuyts, and the editors. FitzGerald and Vos are with the Institute of Social Studies, The Hague. Index.